Effects of fiber or probiotic yogurt supplementation on intestinal barrier integrity in constipation predominant irritable bowel syndrome - Ünsal, Nuket Emine; Akbulut, Gamze; Gülşen, Mustafa (Gülhane tıp dergisi, 2024)
Aims: This study aimed to evaluate the effects of different dietary treatments on intestinal integrity in female subjects aged 19-50 years with a previous diagnosis of constipation-predominant irritable bowel syndrome (IBS). Methods: This randomized controlled trial was conducted at the Gastroenterology Clinic of Gulhane Training and Research Hospital, Ankara, Turkiye. Individuals with IBS were randomly assigned to three groups. Group 1 received a regular constipation diet (n=21), group 2 received a constipation diet rich in soluble fiber (n=17), and group 3 received a constipation diet supplemented with probiotic yogurt (n=22). All participants were followed up for 8 weeks. Intestinal integrity was assessed using plasma zonulin levels before and after treatment. Results: The study included 60 patients (age, mean [+ or -] SD 38.3 [+ or -] 8.1 years). Following the intervention, zonulin levels showed non-significant increases from 24.41 [+ or -] 25.10 to 28.59 [+ or -] 24.05' (p=0.434) in group 1 and 25.91 [+ or -] 25.10 to 28.59 (p=0.758) in group 2. It showed a non-significant decrease from 26.37 [+ or -] 24.22 to 24.44 [+ or -] 22.22 (p=0.393) in group 3. Fasting blood glucose, C-reactive protein, total cholesterol, low-density lipoprotein cholesterol, and triglyceride levels also showed no significant differences between the groups at the beginning and end of the study. There was no significant relationship between zonulin levels and nutrient levels in group 1 and group 3 at the 8th- week measurements. In group 2, zonulin level was inversely and moderately correlated with fat percentage, monounsaturated fatty acid content, and vitamin E content (p<0.05). There was a linear, moderate relationship between zonulin levels and omega 6/omega 3 ratio (r=0.582; p=0.015). Conclusions: The serum zonulin levels did not change significantly after consumption of fiber or probiotic yogurt (NCT06421922). Keywords: Irritable bowel syndrome, soluble fiber, probiotic, intestinal barrier integrity, zonulin